2019
DOI: 10.1109/jstars.2019.2938221
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of VIIRS Detector-Level and Band-Averaged Relative Spectral Response Differences Between S-NPP and NOAA-20 on the Thermal Emissive Bands

Abstract: The Joint Polar Satellite System-1 (renamed NOAA-20 after reaching the polar orbit) was successfully launched on November 18, 2017, into an afternoon orbit with a local equator crossing time of ∼1:30 P.M., in the same orbital plane as the Suomi National Polar-orbiting Partnership (S-NPP) but with a time separation of 50 min. The NOAA-20 Visible Infrared Imaging Radiometer Suite (VIIRS) will become the primary operational imager succeeding the VIIRS onboard S-NPP, which has been in orbit for more than six years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Quantitative metrics have been based on pattern evaluation and structural similarities versus on data from observed measurements. Lin and Cao (2019) demonstrated that the relative spectral responses (RSR) in the IR spectrum for VIIRS on these satellite are not identical, differing between 0.18 K -0.06 K. However, this minimal difference in sensor sensitives is within documented performance limits and thus data from VIIRS off both systems was included when creating the training and validation data set. Additionally, although there are both seasonal and latitudinal variations of the standard atmosphere profile causing differing RSRs in the temporal and spatial region of study, we chose to accept these differences as within reasonable limits for data.…”
Section: Machine Learning For Nighttime Visible Imagerymentioning
confidence: 99%
“…Quantitative metrics have been based on pattern evaluation and structural similarities versus on data from observed measurements. Lin and Cao (2019) demonstrated that the relative spectral responses (RSR) in the IR spectrum for VIIRS on these satellite are not identical, differing between 0.18 K -0.06 K. However, this minimal difference in sensor sensitives is within documented performance limits and thus data from VIIRS off both systems was included when creating the training and validation data set. Additionally, although there are both seasonal and latitudinal variations of the standard atmosphere profile causing differing RSRs in the temporal and spatial region of study, we chose to accept these differences as within reasonable limits for data.…”
Section: Machine Learning For Nighttime Visible Imagerymentioning
confidence: 99%
“…In VIIRS JPSS1, the non-uniformities increase with source temperature [96], which could also be related to differences in spectral response. These detector-to-detector differences in the spectral response of VIIRS lead to detector-to-detector variations in retrieved temperature of up to 7 mK [97]. By comparison, the detector-todetector differences in ECOSTRESS brightness temperatures are up to 375 mK in the 8.78 and 10.49 µm bands and up to 875 mK in the 12.09 µm band (Figure 13).…”
Section: Radiometric Noise (Temporal and Spatial Noise)mentioning
confidence: 99%